2020
DOI: 10.1155/2020/8125392
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intelligent System for Brain Tumor Diagnosis Based on a Composite Neutrosophic-Slantlet Transform Domain for Statistical Texture Feature Extraction

Abstract: Discrete wavelet transform (DWT) is often implemented by an iterative filter bank; hence, a lake of optimization of a discrete time basis is observed with respect to time localization for a constant number of zero moments. This paper discusses and presents an improved form of DWT for feature extraction, called Slantlet transform (SLT) along with neutrosophy, a generalization of fuzzy logic, which is a relatively new logic. Thus, a novel composite NS-SLT model has been suggested as a source to derive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Step IX: End. From Table 6 and Equations ( 23) and (24), SVN-IS and SVN-AIS are determined. The resultant ranking of EVCS sites by SVN-TOPSIS 67 is presented in Table 11.…”
Section: Comparison and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step IX: End. From Table 6 and Equations ( 23) and (24), SVN-IS and SVN-AIS are determined. The resultant ranking of EVCS sites by SVN-TOPSIS 67 is presented in Table 11.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Khan et al 23 proposed`an innovative dispersion control chart based on neutrosophic mean deviation and discussed its enviable properties. Wady et al 24 suggested neutrosophy-based brain tumor intelligent screening system for statistical texture features extraction.…”
mentioning
confidence: 99%
“…This finding indicated that the degree of homogeneity in an oligodendroglioma is lower compared with an astrocytoma ( 45 ). Besides, features belonging to Gray Level Run Length are often applied to distinguish malignant and benign brain tumors ( 46 ). In our model, these features (Long Run High Gray Level Emphasis and Short Run Low Gray Level) were crucial for predicting the status of 1p/19q co-deletion due to the difference in prognostic outcomes between oligodendroglioma and astrocytoma ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Where 𝑔̅ (𝑚,𝑛) is the local mean window size pixels. The probability that the pixel P(m,n) belongs to indeterminate set 𝐼(𝑚, 𝑛) can be calculated using (11) [ 53]:…”
Section: Alow-bestmentioning
confidence: 99%
“…Finally, the probability that the pixel P(m,n) belongs to background (non-white group) 𝐹(𝑚, 𝑛) can be calculated using eq. ( 13) [ 53]:…”
Section: Alow-bestmentioning
confidence: 99%